Utilization of Productive Zakat and its Effect on Empowerment of Small Micro Business (SMEs) in Serang Regency - Najmudin Najmudin; Syihabudin Syihabudin; Ahmad Fatoni; Sujai Sujai (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2021)
This study aims to analyze (1) Utilization of productive zakat in BAZNAS Serang Regency and (2) The effect of the utilization of productive zakat in the form of capital on the empowerment of Small Micro Enterprises (SMEs) in Serang Regency. The object of this research is the National Amil Zakat Agency (BAZNAS) of Serang Regency and Small Micro Enterprises (SMEs) that receive venture capital assistance from BAZNAS Serang Regency. The method used in this study is a mixed-method with a sequential explanatory approach, collection and analysis of qualitative data in the first stage, then followed by the collection and analysis of quantitative data in the second stage. The findings of this study show that (1) Utilization of productive zakat BAZNAS Serang Regency is done through small business capital assistance program given to seven types of small micro-enterprises (SMEs) namely stalls, machete craftsmen, traders, herbal therapy/herbal traders, culinary, sandal name making and travel. Small business capital assistance is distributed in the form of rolling capital loans using qardul hasan contract (repayment amount according to the loan amount), if there is business bankruptcy due to default of SMEs actors, then BAZNAS Serang will resolve it through a partner from local village officials, but if the bankruptcy occurs without any element of default, then BAZNAS Serang Regency will remove SMEs from the nominative if the assistance period has exceeded 5 years. and (2) the utilization of productive zakat in the form of business capital has a positive and significant effect on the empowerment of SMEs in Serang Regency with an influence contribution of 22.7% and the remaining 77.3% is influenced by other factors not examined in this study. Keywords: Empowerment, Productive Zakat, Small and Micro Enterprises (SMEs).